Synergy of design thinking and process transformation approaches - E. V. Vasilieva; T. E. Tochilkina (Управление)
One of the current digitalization trends is focusing on studying customer experience. At present, when managing personnel, it is necessary to analyse and correctly plan the employee’s path in the company - “Employee Experience”. Properly thought out work environment and business processes, focused not only on clients but also on employees, create a good psychological climate. This, in turn, helps the employee to efficiently solve tasks, get business results, show and be focused on developing their talents. The synergy of design thinking, process transformation and continuous improvement approaches will help to change the organization’s culture, create partnerships between staff and management to ensure the success of the changes.The stages of the process transformation, after the completion of which a cycle of continuous improvement of business processes that underwent transformation begins, have been presented in the article. It has been noted, that design thinking techniques can be used for the development and reengineering of not only products (in the usual sense, as a product or service), but also in principle, technology of activity as such (processes). An example of embedding design thinking methods in the process transformation has been given: HMW, Customer Journey Map, The World Caf6, Current-Future-Barriers, Matrices of positive and negative experience. To demonstrate the incorporation of design thinking methods, one of the most capacious stages of the process transformation was chosen - process design. The presented example of the application of design thinking methods for designing business processes can be detailed after clarifying the features of a particular proj ect, supplemented by other design thinking methods, as well as techniques from the arsenal of continuous improvement and process transformation.